Operation Victory - De Guingand, Francis Sir, Major Gen. (Lahore, Pakistan National Book Foundation, 1950)
Marshal Montgomery's Chief of Staff records his experiences from a visit to France and Germany in 1937 through World War.
Include Index, Appendix and Maps
Keywords: World War (1939-1945) -- World War, 1939-1945 -- Personal narratives, English